Trabecular bone properties in the ilium of the Middle Paleolithic/Middle Stone Age Border Cave 3 Homo sapiens infant and the onset of independent gait. Issue 155 (June 2021) - Tommy, Kimberleigh A.; Zipfel, Bernhard; Kibii, Job; Carlson, Kristian J.
Abstract: The Border Cave 3 (BC3) infant skeleton has been understudied, despite its importance as an example of a well-preserved and fairly complete immature skeleton of early Homo sapiens which potentially provides a rare window into various aspects of ontogenetic development, including locomotor activity (e.g., timing of gait events). Trabecular structure in the BC3 ilium was evaluated to investigate whether it matches that of an equivalently aged infant from a postindustrialized society. Microcomputed tomography (μCT) scans were acquired from the BC3 infant and from an ontogenetic series of 25 postindustrial infants that were divided into three age classes (ACs) ranging from neonates to toddlers (<36 months). All ilia were qualitatively compared and then digitally subdivided into 10 volumes of interest (VOIs) based on anatomical reference points. The VOIs were quantified and ontogenetic differences in trabecular structure were statistically evaluated. Across the comparative ontogenetic series, trabecular architectural properties overlapped in all regions. However, trabecular thickness increased significantly after the first year of life. The BC3 infant demonstrated generally similar trabecular structure to that observed in the age-equivalent postindustrial infants (AC2), including relatively strong development of the trabecular chiasma qualitatively. However, some interesting distinctions were observed in BC3, such as low strut thickness compared with infants from the postindustrial sample, that bear further exploration in future studies. Evaluation of only one individual from the Middle Stone Age (MSA), coupled with the relatively small comparative sample, limit our ability to distinguish more meaningful biological differences in trabecular structure throughout ontogeny from idiosyncratic characteristics. Nonetheless, results of this study extend ongoing research on infant locomotor and morphological development to archeological populations in the Middle Stone Age. Further cross-cultural studies consisting of larger comparative postindustrial samples may provide additional information on trabecular structure in the infant ilium during this important developmental timeframe.